Deskripsi Kemampuan Literasi Numerasi Siswa Menggunakan Polya Ditinjau Dari Gender - Bettri Yustinaningrum (JURNAL SINEKTIK, 2021)
The purpose of this study is to examine the numerical literacy ability profile of MI students in class V in terms of gender utilizing Polya problem-solving. In this study, a descriptive qualitative technique was adopted. The research is being conducted at MIN 9 Central Aceh. Purposive sampling is used to choose study volunteers. The data analysis approach developed by Miles and Huberman was employed in this investigation. According to the study's findings, the pupils' numeracy literacy test scores depending on gender have remained in the 40 range, which was classified as poor. According to the findings of the interviews and research, both male and female students struggled to comprehend the problem at the beginning. Male and female students are unable to create solutions, execute solutions, or review replies because they do not grasp the problem.